The Association Between Corporate Governance and Environmental Sustainability Reporting GRI - Debora Anisus Nainggolan; Hilda Rossieta (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the association between corporate governance and environmental environmental sustainability reporting based on the Global Reporting Initiative (GRI) standard. In the modern business era, environmental sustainability reportingis not only a form of corporate accountability to the environment, but also an indicator of transparency and corporate responsibility. This study uses a quantitative approach with secondary data from annual reports and sustainability of public companies listed on the Indonesia Stock Exchange. Governance variables are measured through ownership structure and board composition, while GRI reporting is analyzed based on the environmental disclosure index. The results showed that corporate governance has a significant positive association with the level of disclosure of environmental environmental sustainability reporting. The findings reinforce the view that good governance practices can encourage companies to be more responsible for the environmental impacts of their operations. This research provides implications for regulators, investors, and corporate management in encouraging integration between effective governance practices and transparent and accountable environmental sustainability reporting.